Ethical Challenges and Bureaucratic Impartiality of Civil Servants in the 2024 Simultaneous Regional Elections in Bima City - Ishaka, Mukhlis; Nurfarhati; Haeril; Kasman (KOMUNITAS, 2024)
This study examines political pressure on Civil Servants (ASN) during the 2024 Simultaneous Regional Elections (Pilkada Serentak) in Bima City, focusing on ethical dilemmas that threaten bureaucratic neutrality. ASN are expected to remain neutral, but often face political pressures from local elites, creating conflicts between regulatory compliance and demands to support specific candidates, which undermines bureaucratic credibility. Using a qualitative descriptive method, data were collected through in-depth interviews and observations of political dynamics. The analysis shows that ASN frequently encounter political pressure, leading to ethical conflicts that erode their independence. Career threats further complicate their ability to resist such pressures. The lack of understanding about neutrality regulations worsens the situation, affecting public service quality and local democracy. The study offers insights into reforms to strengthen bureaucratic neutrality and support fair democratic processes in Bima City.